2021
DOI: 10.1007/s11033-021-06223-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cotton leaf curl Multan virus and associated betasatellites with leaf curl disease of Bhut-Jolokia chillies (Capsicum chinense Jacq.) in India

Abstract: Geminiviridae comprises the largest family of plant viruses which causes severe crop losses in India. The highest pungency chilli Bhut-Jolokia or ghost pepper (Capsicum chinense Jaqc.) hails from North-East region of India and is used in many dishes to add flavors and also for its medicinal value. However, this chilli variety is also affected by viruses leading to crop and economic losses. The present study reports the identification of begomoviruses in the infected chilli Bhut-Jolokia leaf samples collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Several factors including enhanced viral replication, mixed infections, increased host range, and vector are known to significantly regulate the recombination ( Qadir et al 2019 ). High frequencies of recombination detection in CP and Rep gene have been previously reported for cotton-infecting begomoviruses ( Saleem et al 2016 ), while for others, CP has been the hot spot of recombination ( Yogindran et al 2021 ). Recently, it has been demonstrated that several resistant-breaking variants of CLCuMuV and other cotton-infecting begomoviruses displayed significant recombination events not only in the viral genomes but also in the associated betasatellites ( Chakrabarty et al 2020 ).…”
Section: Discussionmentioning
confidence: 89%
“…Several factors including enhanced viral replication, mixed infections, increased host range, and vector are known to significantly regulate the recombination ( Qadir et al 2019 ). High frequencies of recombination detection in CP and Rep gene have been previously reported for cotton-infecting begomoviruses ( Saleem et al 2016 ), while for others, CP has been the hot spot of recombination ( Yogindran et al 2021 ). Recently, it has been demonstrated that several resistant-breaking variants of CLCuMuV and other cotton-infecting begomoviruses displayed significant recombination events not only in the viral genomes but also in the associated betasatellites ( Chakrabarty et al 2020 ).…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, the association of CLCuMuV with Malvaceae (cotton, okra, hollyhock, hibiscus species), Solanaceae (chilli, tomato), Cucurbitaceae (luffa species) family of crop plants have been extensively studied in India and Pakistan (Figs. 2 , 3 ) [ 39 41 ] . However, the role of satellites in disease-complex has not been elucidated in detail.…”
Section: Discussionmentioning
confidence: 99%
“…The regions of DNA-A, in which recombination is occur were identified as intergenic region (160 and 386 nt recombinations occur), replication-associated protein and AC4 protein (1,733-2,369; 2,552-2,692; 2,571-2,683 nts) respectively. Therefore, the GC plot analysis suggests that PFLCuV associated with leaf curl disease of passion fruit may undergo recombination at below average GC content regions of its genome The literature surveyed also showed similar results in regions having low GC content as potential recombination sites in plant infecting begomovirus (Yogindran et al 2021) and human adenovirus, which may facilitate virus molecules to evolve and also allow a species to increase its host range in a new environmental niche (Robinson et al 2013).…”
Section: Discussionmentioning
confidence: 77%
“…The low GC region in DNA-A of the PFLCuV associated leaf curl disease of passion fruit might serve as potential recombination sites for facilitating the evolution of a virus as documented in many viruses infecting plants and animals (Yogindran et al 2021;Robinson et al 2013). The sequence with high GC content has more stability due to a triple hydrogen bond, stacking interactions between the bases and is also linked with topology and orientation of DNA strands (Ninh 2013;Yogindran et al 2021). A higher number of bonds between bases in a DNA strand, generally requires more energy to break the strand.…”
Section: Discussionmentioning
confidence: 99%